PENGUJIAN PERUBAHAN GAMBARAN EKG DAN TEKANAN DARAH SEBELUM DAN SESUDAH PEMBERIAN OMEGA 3 DAN BEBAN LATIHAN PADA MAHASISWA PEROKOK - Sari Luthfiyah; Dwi Herry Andayani; Liliek Sutjiatie (Poltekkes Kemenkes Surabaya, 2016)
Demographic Institute University of Indonesia said, the number of deaths arising from a disease that was caused by cigarette in 2004, as many as 427,948 people, it means that as many as 1,172 people per day (22.5 per cent) of the total amount death occurred in Indonesia (Bustan Festival, 2007). One of the danger of the result smoking can cause a tendency blood clotting, so it can increase the risk peripheral arterial disease, the occurrence of coronary artery, and stroke. According to Fadilah Supari, cardiologist at Harapan Kita Hospital Jakarta, that those who consume, these platelets omega3 blood () not to break easily or bank. This research done in order to know test result changes the picture ecg and blood pressure before and after the omega3 heart muscles exercise and the burden on students smokers. This Research using experimental method with pure form design